The economic consequences of the recent political changes in China: the new institutional economics perspective - Legiędź, Tomasz (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: Over 30 years ago, Deng Xiaoping had the two-term limit on the presidency inscribed in the constitution of China. It was part of Deng’s plan to institutionalize leadership changes in China, to avoid a return to one-man rule. This solution has ensured political stability which undoubtedly had a positive impact on economic growth in the following decades. However, in March 2018, the National People’s Congress of China approved the removal of the two-term limit on the presidency. Moreover, president Xi Jinping consolidated his political power as the party voted to enshrine his name and political ideology in the party’s constitution — elevating his status to the level of its founder, Chairman Mao. Aim: The purpose of this article is to analyse the impact of recent changes in the political system of China on the Chinese economy as well as the chances for further development of this country. The paper applies the new institutional economics perspective, particularly, the limited and open access orders framework proposed by D.C. North, J.J Wallis, and B.R. Weingast. Results: The article will present arguments proving that recent political changes in China will negatively affect growth and economic development. The concentration of power in the hands of one man could be a symptom of regression of the limited access order, which, according to North, Wallis, and Weingast affects not only the economy but also could increase the risk of violence.